1997
DOI: 10.1074/jbc.272.46.29222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nerve Growth Factor Carboxyl Terminus in Receptor Binding and Conformational Stability

Abstract: The role of the nerve growth factor (NGF) carboxyl terminus in the function of NGF is not well understood. Previous work showed that deletion of residues 112-120 abolished NGF bioactivity. Several mutagenesis studies, however, have localized the binding sites of the two NGF receptors, p75 and TrkA, to other regions of the NGF molecule. To investigate the role of the NGF COOH terminus, we performed a detailed structure-function analysis of this region by deleting stepwise each of the nine COOH-terminal residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…This is consistent with previous observations (16,46,47). Also, important NGF-p75 interactions are mediated by NGF amino acids 30 -35 within the AЈ-AЉ ␤-turn (39 -41); and these residues in one NGF protomer seem to pack closely with the C terminus of the other protomer within the NGF dimer (42,43).…”
Section: And Ngf ⅐ Ngf30 Afford Equal Trophic Survivalsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with previous observations (16,46,47). Also, important NGF-p75 interactions are mediated by NGF amino acids 30 -35 within the AЈ-AЉ ␤-turn (39 -41); and these residues in one NGF protomer seem to pack closely with the C terminus of the other protomer within the NGF dimer (42,43).…”
Section: And Ngf ⅐ Ngf30 Afford Equal Trophic Survivalsupporting
confidence: 80%
“…The TrkA receptor mediates all of the trophic and neuritogenic activities of NGF whether or not p75 is expressed (13)(14)(15) or bound by the ligand (16,17). However, co-expression of p75 affects ligand affinity and TrkA efficacy (11,13) and also affects ligand-induced internalization (18).…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 99%
“…Deletion studies have also identified the N terminus (22)(23)(24) and C terminus (25)(26)(27) as necessary for TrkA binding. NGF binding to p75 is mainly mediated by the positively charged residues Lys 32 , Lys 34 , and Lys 95 (28) and the reverse-turn residues Asp 72 , Lys 74 , and His 75 (29).…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 99%
“…Loop 1 consists of the previously mapped residues 29 -35, and subsequent studies confirmed that region 29 -35 synthetic peptides inhibited NGF activity and NGF p75 receptor binding (16). Recombinant substitution studies indicated that residues Lys 32 and Lys 34 (17) and other residues (18) are likely to interact with p75 receptors. The NGF sites interacting with TrkA have also been derived via chemical modification (11,19,20), recombinant protein (18, 20 -23), and NGF-TrkA co-crystallization approaches (24).…”
mentioning
confidence: 99%